Attachment as a Predictor of Psychological and Sexual Wellbeing Among Transgender Women in New York City. Issue 9 (22nd November 2019) - Sizemore, K. Marie; Carter, Joseph A.; Millar, Brett M.; Cain, Demetria; Parsons, Jeffrey T.; Rendina, H. Jonathon
Abstract : Transgender women are disproportionately affected by HIV and experience high rates of depression and anxiety. The importance of secure attachment in buffering against negative sexual and mental health outcomes is well established. However, few studies have examined attachment among transgender women. We recruited a community-based convenience sample of 213 transgender women in New York City ( Mage = 34.3; SD = 11.7). The majority were women of color (75.6%), almost half identified as heterosexual (47.4%), and 34.7% were HIV-positive. Preliminary analyses examined the sample distribution across attachment categories using the Revised Experiences in Close Relationships scale. Specifically, Brennan, Clark and Shaver's guidelines were used for categorization (43.19% fearful, 22.5% preoccupied, 21.6% dismissive, and 12.7% secure). Regression analyses examined the association of dimensional attachment anxiety, attachment avoidance, and their interaction with depression, anxiety, self-efficacy for condom use, temptations for condomless sex, and condomless sex acts. Results indicated a positive association between attachment anxiety and depression, anxiety, temptations and probability for condomless sex; and also between attachment avoidance and condomless sex probability. A significant interaction indicated that individuals with low attachment anxiety and attachment avoidance (i.e., secure) had the greatest condom use self-efficacy and the lowest probability of engaging in condomless sex.